Effect of three different preparation designs on the marginal adaptation of indirect overlay restoration fabricated from lithium disilicate ceramic material: An in-vitro comparative study - Sajad Athab Hasan; Zainab Mohammed-Hussain (Elsevier, 2023)
Objectives: Marginal adaptation is considered one of the key factors influencing the success of indirect restorations. This study aimed to estimate the marginal fit of lithium disilicate overlays with three distinct preparation designs before and after cementation. Methods: Thirty maxillary first premolars were divided into the hollow chamfer design (HCD11 HCD: Hollow Chamfer Design.) group, butt-joint design (BJD22 BJD: Butt-Joint Design.) group, and conventional occlusal box design (COD33 COD: Conventional Occlusal Design.) group (n = 10 each). The samples were scanned using an intra-oral scanner, and overlays were fabricated using computer-assisted design and milled on a computer-assisted machine. The finished restorations were luted using a self-adhesive resin RelyX Ultimate. The marginal gap was assessed using a digital microscope with 230X magnification power. Statistical analysis was conducted using analysis of variance and post hoc (Bonferroni correction) tests, assuming a significance level of 5%. Results: The HCD and BJD groups recorded significantly lower marginal gap, (11.39 ± 0.72, 16.29 ± 0.75) and (11.59 ± 0.75, 16.93 ± 0.65) respectively, than the COD group (24.57 ± 1.18, 34.45 ± 1.09) both pre- and post-cementation. Conclusion: This study demonstrated that modification of tooth preparation plays a significant role in the marginal adaptation of the lithium disilicate overlays. The gap was smaller with the HCD and BJD than with the COD, with a statistically significant difference.